The Effect of Promotion Mix on Customer Perceptions at Bank Tabungan Negara Syariah (BTNS) Banda Aceh Branch Office - Hajriyanti, Rahmi; Rizal, Syamsul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
One of the marketing elements that influences customer behavior is product management and promotion mix. Product management emphasizes that customers need certain types and service facilities, while promotion mix is ​​a promotional variable that uses a combination of flash, publicity, sales promotion and personal selling. It is hoped that customer perception can increase, by increasing the number of promotion mixes. The aim of this research is to determine the effect of the promotion mix on customer perceptions at the BTNS Bank Banda Aceh Branch Office. To obtain the required data and information, research was carried out directly at the Operational office of Bank BTNS (Bank Tabungan Negara Syariah), Jl. Daud Bereueh, Banda Aceh. The object of this research is the influence of Promotion Mix on customer perceptions, while the respondents in this research were 100 people. Simultaneous research results show that all the variables studied have a significant effect on customer perceptions at Bank BTNS Banda Aceh Branch, this is because the Fcount > Ftable value is obtained at a significance level of α = 5%. Meanwhile, partially (as a whole) the influence of the variables advertising (X1), publicity (X2), selling personnel (X3), Sales Promotion (X4) has a significant influence on customer perceptions of Bank BTNS Banda Aceh Branch.